Structural basis of Zika virus methyltransferase inhibition by sinefungin - Hercik, Kamil; Brynda, Jiri; Nencka, Radim; Boura, Evzen (Archives of virology, 2017)
Zika virus is considered a major global threat to human kind. Here, we present a crystal structure of one of its essential enzymes, the methyltransferase, with the inhibitor sinefungin. This structure, together with previously solved structures with bound substrates, will provide the information needed for rational inhibitor design. Based on the structural data we suggest the modification of the adenine moiety of sinefungin to increase selectivity and to covalently link it to a GTP analogue, to increase the affinity of the synthesized compounds.
Keywords: Protein Binding; molekulární modely; adenosin; Zika Virus; Models, Molecular; vazba proteinů; Binding Sites; virus zika; methyltransferasy; vazebná místa; Adenosine; Enzyme Inhibitors; inhibitory enzymů; Methyltransferases